2019
DOI: 10.1016/j.aott.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 3-T MRI and CT findings with patient symptoms and treatment outcome in radiofrequency ablation of osteoid osteoma

Abstract: ObjectiveThe aim of this prospective study was to evaluate pre- and post-treatment MRI and CT findings of osteoid osteoma (OO) patients treated with radiofrequency thermo-ablation (RFTA) and to compare these findings with visual analog scale (VAS) scores.MethodsSixteen patients (4 females and 12 males; mean age of 18.87 ± 8.75 years (range: 8–37)) with OO were examined with CT and MRI, at baseline and at an average of 3 months following the procedure. On pre- and post-procedural CT and MRIs, OO-related finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In our collective experience this may not be required in routine procedures or benign lesions such as OOs unless the patient reports persistent or new-onset symptoms. Postintervention imaging includes assessment of the volume of the tumor, 15,29,30 cortical thickening, periostitis and/or a periosteal reaction, bone or soft tissue deformity, tumoral signal changes, adjacent bone marrow and/or soft tissue edema, cortical or medullary sclerosis, 31 joint effusion, synovitis, contrast enhancement patterns, or presence of locoregional lymph nodes. Imaging protocols should ideally match the preprocedural studies to minimize any bias that could be introduced by technical factors.…”
Section: Postinterventionmentioning
confidence: 99%
“…In our collective experience this may not be required in routine procedures or benign lesions such as OOs unless the patient reports persistent or new-onset symptoms. Postintervention imaging includes assessment of the volume of the tumor, 15,29,30 cortical thickening, periostitis and/or a periosteal reaction, bone or soft tissue deformity, tumoral signal changes, adjacent bone marrow and/or soft tissue edema, cortical or medullary sclerosis, 31 joint effusion, synovitis, contrast enhancement patterns, or presence of locoregional lymph nodes. Imaging protocols should ideally match the preprocedural studies to minimize any bias that could be introduced by technical factors.…”
Section: Postinterventionmentioning
confidence: 99%
“…Recently, dynamic contrast-enhanced MRI has also been described as a useful tool for visualization of short-term healing following thermal ablation of OO (36)(37)(38). Despite the wide range of imaging options, however, the long-term response to therapy has to be evaluated by clinical followup and patient-reported outcome measures, in particular subjective pain (39).…”
Section: Discussionmentioning
confidence: 99%
“…Yuce et al (65) reported osteomyelitis caused by burn infection caused by needle overheating. Kaptan et al (57) documented a case of local osteomyelitis without cause. Based on the foregoing, several measures can be implemented to prevent the occurrence of serious complications and thus improve the safety of surgical treatment, such as preoperative iodine coating to prevent postoperative infection (71), reducing bone defects during operation, limiting exercise within 3 months after the operation, using sterile ice packs to cool the surrounding skin during percutaneous ablation or inserting additional needles to infuse saline to protect peripheral nerves (72, 73), or multiple low power ablations.…”
Section: Discussionmentioning
confidence: 99%